Mastering Web Services Security - Hartman, Bret (Wiley Publishing, 2011)
Uncovers the steps software architects and developers will need to take in order to plan and build a real-world, secure Web services system Authors are leading security experts involved in developing the standards for XML and Web services security Focuses on XML-based security and presents code examples based on popular EJB and .NET application servers Explains how to handle difficult-to-solve problems such as passing user credentials and controlling delegation of those credentials across multiple applications Companion Web site includes the source code from the book as well as additional examples and product information